2005
DOI: 10.1021/jp040549a
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive DFT Study of Nitrous Oxide Decomposition over Fe-ZSM-5

Abstract: The reaction mechanism for nitrous oxide decomposition has been studied on hydrated and dehydrated mononuclear iron sites in Fe-ZSM-5 using density functional theory. In total, 46 different surface species with different spin states (spin multiplicity M(S) = 4 or 6) and 63 elementary reactions were considered. Heats of adsorption, activation barriers, reaction rates, and minimum energy pathways were determined. The approximate minimum energy pathways and transition states were calculated using the "growing str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
193
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(218 citation statements)
references
References 65 publications
21
193
3
1
Order By: Relevance
“…(2) has been favoured for a long time [8,14,15,19] in agreement with findings in a fixed bed reactor under steady state conditions [15]. However, recent studies have shown that also the O 2 desorption can determine the rate of total N 2 O decomposition [26,27], in concordance with DFT-model calculations [28]. Finally, the reaction of N 2 O with surface oxygen (Eq.…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…(2) has been favoured for a long time [8,14,15,19] in agreement with findings in a fixed bed reactor under steady state conditions [15]. However, recent studies have shown that also the O 2 desorption can determine the rate of total N 2 O decomposition [26,27], in concordance with DFT-model calculations [28]. Finally, the reaction of N 2 O with surface oxygen (Eq.…”
Section: Introductionsupporting
confidence: 82%
“…Thus, the surface oxygen amount, calculated by the N 2 formed, increases with higher reaction temperatures (Table 3). Wood et al [19] and Perez-Ramirez et al [8,26] also found this effect on ZSM5 zeolites containing 0.38% Fe (w/w) and 0.68% Fe (w/w), respectively, in the range of 500-573 K. In contrast, Kiwi-Minsker et al [16] observed no influence of the reaction temperature for zeolites containing ≤1000 ppm Fe (w/w) in the range of 523-603 K. A possible explanation could be that the temperature increases the number of active iron species in the Fe-MFI, particularly in zeolites [27,28] and by Kondratenko and Perez-Ramirez [26], or the formation of oxygen species bound to different sites. DFT calculations in Refs.…”
Section: Step Techniquementioning
confidence: 96%
See 3 more Smart Citations